Ocena efektywności kosztów w przedsiębiorstwie - Krajewski, Mirosław (Evaluation of Cost Effectiveness in Enterprise, 2005)
The managers of a company, in the process of evaluating economic activity, should analyze the costs and study their effectiveness from the point of productivity and remunerative, towards the growth of the value of a firm. The main factor which has an influence upon remunerative of the cost is the scale of sale. It is determined by the company. The increase of the costs of a company resulting in the increase of net profits influences the growth of remunerative of the company capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 214-224